Patterns of wisdom in the Old English "Solomon and Saturn II". - Wallis, Mary V. (University of Ottawa (Canada), 1991)
The Old English Solomon and Saturn II has received virtually no extended critical commentary since Robert J. Menner's 1941 edition of it and its companion piece, Solomon and Saturn I. The few brief attempts made to explain the poem, moreover, have been without reference to the body of OE sapiential thought to which it belongs. This thesis offers a close structural and thematic reading of SS II as it appears against the background of general notions and concepts belonging to the body of OE wisdom. The thesis begins with a review of the poem's history and related literary criticism. Lexical and thematic material is then selected from the entire OE corpus to present those aspects of OE wisdom that bear on an understanding of SS II. The thesis addresses the conceptual and intellectual formulations of wisdom in the Anglo-Saxon period, rather than simply its literary forms, and it takes into account both pre-conversion and Christian views on human and divine wisdom. The thesis then illustrates how SS II reflects certain patterns that exist in the general OE wisdom tradition. The narrator's framework establishes a metaphysical context for the whole poem that is consistent with the Christian Anglo-Saxon concept of divine Wisdom. The epistemological premises of the debate itself, as well as a core of beliefs and implicit assumptions shared by the opponents, Solomon and Saturn, reflect the tensions and harmonies that appear in the broad view of OE wisdom. The interaction between Saturn and Solomon--the one a travelling Chaldean noble, the other the Old Testament King, is examined next. The competition between an epic rhetorical model, namely, the visit of a roving hero to the court of an established king, and the Christian typology that surrounds the wise King Solomon, is arguably a significant source of meaning in the poem. The tension between literary and figural patterns provides an interpretive matrix against which the audience can follow the discourse of the two men. Finally, the thesis turns to the structure of the SS II dialogue and demonstrates that far from being a simple contest of wit and "wisdom," the poem is a sophisticated process of education through dialogue whose central concern is the emancipation of the mind from the illusions of language. The dialogue shares several "habits of thought" with Boethius' Consolation Philosophiae and Augustine's Soliloquia in the process by which it restores to Saturn's infirm and misguided mind its natural wisdom and its power of interpretation.
Keywords: Literature, Medieval.